(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics and treatment outcomes of patients with CIN II, CIN III, and CIS treated with LEEP or CKC. Methods: A retrospective study was conducted on 290 patients treated with LEEP or CKC at the National Hospital of Obstetrics and Gynecology from January 2022 to December 2024. Results: Among 290 patients, most were of reproductive age (25–39 years, 65.2%), and 30.0% were ≥40 years; the majority had children (66.6% with 1–2 children). Cytological abnormalities were common, including ASCUS in 21.4%, LSIL in 20.7%, and HSIL in 22.8%. HPV 16 was the most frequent type (44.5%). Histopathology after treatment was consistent with initial biopsy in 83.8% of cases. Upgrading of lesions was mainly observed in the CIN II group (22.1%, p < 0.001). In multivariable analysis, treatment method, final histopathological diagnosis, and discrepancy between initial biopsy and final diagnosis were independently associated with positive surgical margins. Conclusion: LEEP and cervical cone biopsy are the two main treatment methods for CIN lesions. Combining colposcopy with biopsy to accurately diagnose the extent of the lesion, along with selecting the appropriate treatment method based on each patient’s characteristics, may contribute to improving treatment effectiveness.